Concomitant cutaneous metastatic tuberculous abscesses and multifocal skeletal tuberculosis - Sezgin Betul; Atilganoglu Ulviye; Yigit Ozgul; Ergun Selma; Cambaz Nevin; Demirkesen Cuyan (Wolters Kluwer Medknow Publications, 2008)
Tuberculosis, one of the oldest diseases known to affect humans is caused by the bacteria mycobacterium tuberculosis. The disease usually affects the lungs, although, in up to one third of cases, other organs are involved. Metastatic tuberculosis abscess is a rare form of skin tuberculosis. It is characterized by nodule and abscess formation throughout the body after hematogenous spread of mycobacterium tuberculosis from a primary focus during a period of impaired immunity. Tuberculosis osteomyelitis is also a rare form of extrapulmonary tuberculosis in pediatric age group. Skeletal tuberculosis pathogenesis is related to reactivation of hematogenous foci or spread from adjacent paravertebral lymph nodes. Weight-bearing joints are affected most commonly. Bilateral hand and foot bone involvement is rarely reported. We present a five-year-old girl with two very rare presentations of the disease such as osteomyelitis and metastatic skin abscess.